2015
DOI: 10.1371/journal.pone.0129343
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 70 Prevents Hyperoxia-Induced Disruption of Lung Endothelial Barrier via Caspase-Dependent and AIF-Dependent Pathways

Abstract: Exposure of pulmonary artery endothelial cells (PAECs) to hyperoxia results in a compromise in endothelial monolayer integrity, an increase in caspase-3 activity, and nuclear translocation of apoptosis-inducing factor (AIF), a marker of caspase-independent apoptosis. In an endeavor to identify proteins involved in hyperoxic endothelial injury, we found that the protein expression of heat-shock protein 70 (Hsp70) was increased in hyperoxic PAECs. The hyperoxia-induced Hsp70 protein expression is from hspA1B gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…It is involved in protein import into organelles, such as mitochondria and endoplasmic reticulum [47]. Recently, it has been reported that hyperoxia can induce an increase in HSP70 expression due to formation of ROS [48]. Similar with these findings, NBO induced upregulation of HSP70 in our study.…”
Section: Stress Response and Proteostasissupporting
confidence: 91%
“…It is involved in protein import into organelles, such as mitochondria and endoplasmic reticulum [47]. Recently, it has been reported that hyperoxia can induce an increase in HSP70 expression due to formation of ROS [48]. Similar with these findings, NBO induced upregulation of HSP70 in our study.…”
Section: Stress Response and Proteostasissupporting
confidence: 91%
“…Another study demonstrated that enhanced Hsp70 expression attenuates apoptosis in ALI [30]. Moreover, HSP70 overexpression inhibits caspase-3 activation and PARP cleavage [31,32].…”
Section: Discussionmentioning
confidence: 97%
“…Damage occurs to the lung endothelial cells, leading to barrier disruption between the lung surface and the vasculature . In studies investigating the connection between hyperoxia and lung barrier disruptions, researchers demonstrated increased HSP72 protein expression in pulmonary artery endothelial cells exposed to 95% oxygen and specific inhibition of the ATP‐dependent, caspase‐directed apoptosis pathway and the ATP‐independent AIF pathway by HSP72. Disruption of HSP72 activity, either with a general heat shock protein inhibitor (KNK437) or specific disruption using siRNA, increased endothelial cell apoptosis as measured by TUNEL assay, caspase‐3 activity, and AIF translocation from the cytoplasm into the nucleus.…”
Section: Hsp72 As a Pulmonary Cytoprotectantmentioning
confidence: 99%
“…This long induction period may have evolved in order to deliver a chronic cytoprotectant to the cells following an acute injury in which secondary effects, such as apoptosis, can occur hours later. In the case of hyperoxic exposure of the lungs, HSP72 induction reaches its maximum 24 h after exposure . Hyperoxia causes a biphasic barrier disruption of the endothelial monolayer, with the first phase occurring 1–3 h after exposure and the second phase, largely attributable to apoptosis, occurring at 24 hours .…”
Section: Hsp72 As a Pulmonary Cytoprotectantmentioning
confidence: 99%
See 1 more Smart Citation